Characterization of stress degradation products of blonanserin by UPLC-QTOF-tandem mass spectrometry1. Issue 85 (16th September 2015) - Kalariya, Pradipbhai D.; Patel, Prinesh N.; Sharma, Mahesh; Garg, Prabha; Srinivas, R.; Talluri, M. V. N. Kumar
<x xml:space="preserve">Abstract</x> Forced degradation study of blonanserin and structural elucidation of its degradation products was performed using high resolution tandem mass spectrometry.